2005
DOI: 10.1124/jpet.105.093500
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cannabinoid Peripheral Cannabinoid Receptor-Selective Inverse Agonist Blocks Leukocyte Recruitment in Vivo

Abstract: The expression of the cannabinoid peripheral cannabinoid receptor (CB 2 ) receptor on peripheral immune cells suggests that compounds specific for CB 2 might be effective anti-inflammatory agents. In this report, we present the initial biological profiling of a novel triaryl bis-sulfone, Sch.336, which is selective for the human cannabinoid CB 2 receptor (hCB 2 ). Sch.336 is an inverse agonist at hCB 2 , as shown by its ability to decrease guanosine 5Ј-3-O-(thio)triphosphate (GTP␥S) binding to membranes contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 38 publications
2
96
0
1
Order By: Relevance
“…Furthermore, autoactivation may underlie the lack of significant stimulation of neutrophil migration by the CB 2 receptor agonists 2-AG, CP55940, JWH-133, and JWH015 (Kurihara et al, 2006; this study). In line with our findings, Lunn et al (2006) have demonstrated that CB 2 receptor inverse agonists inhibit leukocyte migration both in vivo and in vitro, and the level of effect is proportional to the degree of inverse efficacy.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, autoactivation may underlie the lack of significant stimulation of neutrophil migration by the CB 2 receptor agonists 2-AG, CP55940, JWH-133, and JWH015 (Kurihara et al, 2006; this study). In line with our findings, Lunn et al (2006) have demonstrated that CB 2 receptor inverse agonists inhibit leukocyte migration both in vivo and in vitro, and the level of effect is proportional to the degree of inverse efficacy.…”
Section: Discussionsupporting
confidence: 76%
“…We also found that SR144528 markedly suppressed the ear swelling induced by dinitrofluorobenzene in mice (S. Oka and T. Sugiura, unpublished results). In contrast, Jan et al (51) and Lunn et al (52) demonstrated that ⌬ 9 -tetrahydrocannabinol and several CB2 receptor antagonists suppressed inflammatory reactions in the airway. These experimental results are generally consistent with the experimental results obtained in the present study and previously (30), although no information is available on 2-AG in these studies by other investigators (50 -52).…”
Section: Discussionmentioning
confidence: 99%
“…This system, insensitive to the pharmacology of potential hit compounds, resulted in the identification of the triaryl bis sulfone class of cannabinoid CB 2 receptor-specific inverse agonist. 7 Efforts to specifically identify cannabinoid CB 2 receptorspecific agonists utilized a recombinant cell-based cAMP competitive immunoassay, the LANCE ™ cAMP Detection Kit from PerkinElmer. To achieve the robustness required for library screening, the recombinant cell biosensor was treated with the kinase inhibitor tangeretin, 8 which improved the signal-to-background ratio achieved using this platform.…”
Section: Resultsmentioning
confidence: 99%